2017
DOI: 10.1039/c7mb00082k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleobase change on cytosine deamination through DNA photo-cross-linking reaction via 3-cyanovinylcarbazole nucleoside

Abstract: Photo-chemical deamination of cytosine using 3-cyanovinylcarbazole nucleoside (K) mediated photo-cross-linking is a technique for site-directed mutagenesis. Using this technique in vivo requires the elimination of a high-temperature incubation step; instead, incubation should be carried out under physiological conditions. To improve the reactivity of K mediated photo-cross-link induced deamination of cytosine under physiological conditions, an evaluation of base pairing in cytosine was carried out with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…It is interesting to note here that the rate of deamination while using ODN(I CNV K) in 7 days is 4.7 × 10 −3 h −1 , whereas, while using ODN(I OHV K) the rate has increased almost 1.6 folds. This has definitely shown an improvement over our previous results where we obtained ~35% conversion in 3 days [ 27 ] . Also, with ODN(I OHV K<>C), the rate of deamination of cytosine to uracil was 2-fold faster than that with ODN(I NH2V K<>C).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…It is interesting to note here that the rate of deamination while using ODN(I CNV K) in 7 days is 4.7 × 10 −3 h −1 , whereas, while using ODN(I OHV K) the rate has increased almost 1.6 folds. This has definitely shown an improvement over our previous results where we obtained ~35% conversion in 3 days [ 27 ] . Also, with ODN(I OHV K<>C), the rate of deamination of cytosine to uracil was 2-fold faster than that with ODN(I NH2V K<>C).…”
Section: Resultssupporting
confidence: 57%
“…In 2015, we showed the effect of hydrogen bonding on the rate of the photo-cross-linking reaction by changing the counter-base of cytosine [ 26 ], which led to the idea that hydrogen bonding could also play a role in the deamination reaction. In 2017, we further proved our hypothesis by showing that certain counter-bases, especially inosine, of cytosine are better for deamination than other bases due to a specific type of hydrogen bonding in the cross-linked cytosine [ 27 ]. Furthermore, we also reported that not only hydrogen bonding, but also the polarity around the cytosine-photo-adduct, is responsible for the velocity of the deamination reaction at lower temperatures using derivatives of vinylcarbazole [ 28 ].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In attempts to overcome the need for the heating step, we found that deamination can be achieved under physiological conditions by changing the cytosine unit's complementary base from guanine to inosine, leading to differences in hydrogen bonding pattern and spatial orientation, and thus accelerating the deamination reaction . In addition, we also reported that the deamination could be promoted by replacing the vinylcarbazole derivative substituent with a highly hydrophilic substituent .…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the influence of the surrounding environment of the target cytosine on deamination efficiency, we previously examined the various complementary bases of target cytosine and photo-crosslinkers with modified terminal sites. [19][20][21] These photochemical C to U conversions evaluated the conversion efficiency to uracil by targeting cytosine into the DNA strand; though, it is difficult to form the natural DNA double-stranded structure via inversion by a nucleic acid probe. RNA forms a higher-order structure, and thus can form a double strand together with a nucleic acid probe, as happens with antisense nucleic acid.…”
mentioning
confidence: 99%